Calidad de vida de los pacientes con amputación por Diabetes Mellitus. Hospital Minsa II – 2 Tarapoto, Mayo – Noviembre 2016 - Gómez Saldaña, Candy Angélica (2017)
The aim of the following research was to determine the life quality with amputation due to diabetes mellitus, Hospital MINSA II - 2 Tarapoto, 2016, a simple descriptive study, in a sample of 100 patients amputated by diabetes mellitus, Applied the Whoqol-Bref questionnaire. The following results were found: 61.0% of the patients are males, 34.0% of the patients are 49 to 58 years of age, the average age is 58 years with a standard deviation of 10, 3. 40.0% of the patients are married, 93.0% of the patients do have children; 34.0% of patients have completed primary studies, patients have a mean of 8.22 years with diabetes and a standard deviation of 2.8 years. The average number of years that suffered amputation is 3 years with a standard deviation of 1.45 years. The quality of life according to the physical health, psychological health, social relations, and environment dimensions is average. It is concluded that patients with diabetes mellitus amputation have an average quality of life. Hospital MINSA II - 2 Tarapoto. May - November 2016